Sensitivitas Dan Spesifisitas Lingkar Pinggang Dalam Mengidentifikasi Kelebihan Berat Badan Dan Obesitas Pada Wanita Dewasa - Aulia Miladitiya (Poltekkes Kemenkes Surakarta, 2018)
Abstract : Obesity, Overweight, Sensitivity, Specificity, Waist Circumference. Body mass index couldn’t differentiated correlation between body weight with muscle or body fat and indication distribution of body fat. Waist circumference measurement needed because it is convenient and strongly correlated with intra-abdominal fat content. This study aims to assess sensitivity and specificity of waist circumference measurement in identified overweight and obesity on adult women compared with body mass index as gold standard. This Study design is observational with cross sectional approach. Total of 80 women subjects aged >18-49 years old was selected using cluster random sampling. Sensitivity and specificity were analyzed from Receiver Operator Characteristic Curve. Cut-off waist circumference which used to identify overweight and obesity on adult women were >80 cm and >88 cm. The use of 80,1 cm of waist circumference was shown to have a good sensitivity and specificity (82% and 72%). Waist circumference have fair diagnostic power (area under curve was 0,784). Waist circumference can used to identify overweight and obesity because have sensitivity and specificity value good.